2017
DOI: 10.1001/jamaoncol.2016.3358
|View full text |Cite|
|
Sign up to set email alerts
|

Association of Proton Pump Inhibitors and Capecitabine Efficacy in Advanced Gastroesophageal Cancer

Abstract: clinicaltrials.gov Identifier: NCT00680901.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
115
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(121 citation statements)
references
References 21 publications
3
115
3
Order By: Relevance
“…risk of myocardial infarction is higher in patients who have heart failure) and mortality which was obtained from a number of epidemiological studies. [41,42,43,44,45,46,47,48,49,50,51,52]. …”
Section: Methodsmentioning
confidence: 99%
“…risk of myocardial infarction is higher in patients who have heart failure) and mortality which was obtained from a number of epidemiological studies. [41,42,43,44,45,46,47,48,49,50,51,52]. …”
Section: Methodsmentioning
confidence: 99%
“…A total of 353 potentially eligible records were identified in the electronic databases. After exclusion of n=337 not pertinent papers, n=16 were selected for inclusion in quantitative analysis (n=372,418 patients included, with 12% of patients receiving concomitant GAS therapy) [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. The search results and characteristics of the included studies are presented in figure 1 and tables 1-2.…”
Section: Resultsmentioning
confidence: 99%
“…They reported that bevacizumab added to capecitabine with oxaliplatin is an active and well-tolerated regimen for patients with small bowel adenocarcinoma and ampullary adenocarcinoma. 4 In conclusion, the efficacy of capecitabine may be decreased during the concomitant use of PPIs by possibly raising gastric pH levels, thereby leading to alterations in the dissolution and absorption of capecitabine. 2,3 This association with gastric acid suppressants may not be limited to tyrosine kinase inhibitors given that many oral drugs such as capecitabine require a sufficiently acidic environment to properly dissolve for systemic absorption.…”
mentioning
confidence: 97%
“…The authors found that PPIs negatively affected the efficacy of capecitabine. 4 In conclusion, the efficacy of capecitabine may be decreased during the concomitant use of PPIs by possibly raising gastric pH levels, thereby leading to alterations in the dissolution and absorption of capecitabine. Therefore, patients being treated with capecitabine should be questioned as to whether they are receiving concomitant PPIs.…”
mentioning
confidence: 97%
See 1 more Smart Citation